2023
DOI: 10.1186/s12933-023-01867-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mortality in patients with advanced chronic kidney disease with and without diabetes: a nationwide cohort study

Abstract: Background Cardiovascular mortality and the impact of cardiac risk factors in advanced chronic kidney disease (CKD) remain poorly investigated. We examined the risk of cardiovascular mortality in patients with advanced CKD with and without diabetes as well as the impact of albuminuria, plasma hemoglobin, and plasma low-density lipoprotein (LDL) cholesterol levels. Methods In a Danish nationwide registry-based cohort study, we identified persons age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In addition, we observed that SII and SIRI levels were associated with mortality in patients with different underlying diseases, including diabetes, hypertension, and CVD. The results of our analysis are consistent with previous studies: diabetes is a signi cant risk factor for cardiovascular death and death from hypertension [36,37]. Previous studies have described several potential pathways of glycemic status that lead to effects on vascular outcomes associated with oxidative stress, late glycosylation processes, and epigenetic mechanisms, which in turn affect mortality in patients with CKD [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we observed that SII and SIRI levels were associated with mortality in patients with different underlying diseases, including diabetes, hypertension, and CVD. The results of our analysis are consistent with previous studies: diabetes is a signi cant risk factor for cardiovascular death and death from hypertension [36,37]. Previous studies have described several potential pathways of glycemic status that lead to effects on vascular outcomes associated with oxidative stress, late glycosylation processes, and epigenetic mechanisms, which in turn affect mortality in patients with CKD [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…По результатам датского регистра стандартизированный риск общей и сердечнососудистой смертности пациентов с ХБП в течение 1 года зависит от тяжести заболевания (рис. 5) [9].…”
Section: оценка рисков неблагоприятных исходов в группе пациентов с а...unclassified
“…CKD is characterized by a severe decline in kidney function, reduced glomerular filtration rate (GFR), heightened urinary albumin excretion (proteinuria), and confirmed by two or more diagnoses at least 3 months apart ( 5 ). The condition is closely associated with various comorbidities, including diabetes ( 6 , 7 ), hypertension ( 8 , 9 ), obesity ( 10 , 11 ), particularly cardiovascular diseases ( 12 ), and is strongly correlated with an increased all-cause mortality rate ( 13 , 14 ). Beyond significantly impacting patients’ quality of life, CKD also stands as a major contributor to poverty.…”
Section: Introductionmentioning
confidence: 99%